Estudo cinético da produção de ésteres metílicos com dimetil carbonato catalisada por fosfato de nióbio - Alessio, Claudia (2017)
The aim of this study was to evaluate commercial niobium phosphate as heterogeneous catalyst in biodiesel production from oleic acid and low-cost raw materials using dimethyl carbonate as acyl receptor. Catalyst was characterized and textural and structural properties were obtained. Effect of temperature (180°C-250°C), dimethyl carbonate molar ratio (1:5, 1:10, 1:15) and catalyst concentration (2%, 5%, 10%) were investigated. Reactions at 180ºC and 200ºC, in 6 hours, achieved 57% and 75% conversion oleic acid, respectively. Reaction showed a higher reaction rate at 225ºC and 250ºC, reaching equilibrium conversion in about 3 and 2 hours, respectively. At 225 and 250ºC, maximum conversion achieved to oleic acid was 84%. For the range studied, molar ratio was not a determinant variable to increase the oleic acid conversion. Catalyst concentration had a positive effect on esterification reaction, increasing reaction rate and conversion of oleic acid. Most suitable condition was at 3 hours, molar ratio of 1:5, 5% catalyst based on FFA mass and 250°C. Catalyst could be reutilized for up to 5 cycles without significant loss of activity. A pseudo first order model was proposed to esterification of oleic acid. Niobium phosphate activity was carried out for biodiesel production with raw materials of high and low acidity.